1990
DOI: 10.3109/07420529009064636
|View full text |Cite
|
Sign up to set email alerts
|

Heart Rate Orcadian Rhythm as a Biological Marker of Desynchronization in Major Depression: A Methodological and Preliminary Report

Abstract: Heart rate (HR) was continuously monitored during successive 24-hr periods in 19 healthy subjects and 26 major depressed patients (DSM III-R). Recordings were performed after a 2-week wash-out period and the morningness or eveningness typology of each subject was determined. The chronobiological parameters and rhythm percentage (RP) were calculated by the single cosinor method from the smoothed HR curves of each subject. In normal subjects, HR follows a circadian rhythm (RP greater than 65%) with the lowest va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
1

Year Published

1993
1993
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 0 publications
1
2
1
Order By: Relevance
“…Our work does not confirm the phase advance hypothesis of depression (Wehr et al, 1979), as suggested by others (Kripke, 1979;Tsujimoto et al, 1990;Taillard et al, 1992). Nevertheless, in depressed patients, it is possible that their estimation of diurnal preference may be partly biased by the sensation of malaise in the morning, which might in turn modify answers to those items involving morning status and performance (Taillard et al, 1990).…”
Section: Dependentcontrasting
confidence: 87%
“…Our work does not confirm the phase advance hypothesis of depression (Wehr et al, 1979), as suggested by others (Kripke, 1979;Tsujimoto et al, 1990;Taillard et al, 1992). Nevertheless, in depressed patients, it is possible that their estimation of diurnal preference may be partly biased by the sensation of malaise in the morning, which might in turn modify answers to those items involving morning status and performance (Taillard et al, 1990).…”
Section: Dependentcontrasting
confidence: 87%
“…In the violent method group, an anticipated peak in the early afternoon hours was observed (acrophase: 14.31 vs. 16.05 hours for the non-violent method group), similar to the time period that has been found for suicide (7,8). This observation suggests the hypothesis that suicidal behaviours involving more violent methods more closely resemble failed suicide than parasuicide.…”
Section: Discussionsupporting
confidence: 66%
“…Considerable evidence has accumulated which indicates that several alterations in circadian rhythms occur in association with affective disorders and may play a relevant aetiological role. In particular, circadian anomalies have been documented with regard to body temperature ( 14), sleep pattern (15), heart rate ( 16), plasma and urinary cortisol ( 17 ), plasma prolactin ( 18 ) and melatonin (19). Other biochemical dysfunctions to be considered as possible candidates include either catecholamines (20-21) or serotonin (22-23).…”
Section: Discussionmentioning
confidence: 99%
“…Morning types usually wake up several hours earlier than evening types, for example an average of 07:20 versus 09:20 in a study in England [12], although the full spread of chronotypes (95% confidence interval of the mean) was found to be about 6 hours in a more extensive study [13], indicating that most people wake up within a 6-hour window in the morning, with "larks" as early as 6 o'clock and "owls" as late as noon. Consistently with these differences in wake-up time, the daily rhythms of body temperature [1,14,15], heart rate [16,17], and melatonin secretion [15,[18][19][20] peak earlier in the day in morning types than in evening types. Morning types are more alert at wake-up time [3,21], are better at recognition of sentences presented in the morning than in the afternoon [22], are less stressed out by morning commute driving than evening types [23], and prefer having sex earlier in the day than evening types [24].…”
Section: Introductionmentioning
confidence: 81%